Potent Selective Cytotoxic Activity of Kaempferia Galanga L. Rhizome Against Cancer Cell Cultures - JAGADISH P.C.; RAGHU CHANDRASHEKHAR H.; VINOD KUMAR S.; LATHA K.P. (International Journal of Pharma and Bio Sciences, 2010)
Crude ethanol extract of the rhizome Kaempferia galanga L. and the successive extracts prepared with increasing polarity viz., petroleum ether, ethyl acetate and ethanol. The extracts and fractions were screened for cytotoxic activities by standard MTT and SRB assays against four cancerous viz., DU145, PA1, SW620, B16F10 and a normal Vero cell cultures. The successive ethyl acetate extract showed selective toxicity towards cancer cells and showed less toxicity towards normal cells. The successive petroleum ether fraction showed potent activity against human colorectal adenocarcinoma cells with CTC50 0.55 µg/ml and was comparatively non toxic towards normal Vero cell cultures.